We begin at the end ebook - Whitaker, Chris (2021)
Winner of the Gold Dagger for Best Crime Novel from the Crime Writers' Association (UK) Winner for Best International Crime Fiction from Australian Crime Writers Association An Instant New York Times Bestseller "A vibrant, engrossing, unputdownable thriller that packs a serious emotional punch. One of those rare books that surprise you along the way and then linger in your mind long after you have finished it." —Kristin Hannah, #1 New York Times bestselling author of The Nightingale and The Four Winds Right. Wrong. Life is lived somewhere in between. Duchess Day Radley is a thirteen-year-old self-proclaimed outlaw. Rules are for other people. She is the fierce protector of her five-year-old brother, Robin, and the parent to her mother, Star, a single mom incapable of taking care of herself, let alone her two kids. Walk has never left the coastal California town where he and Star grew up. He may have become the chief of police, but he's still trying to heal the old wound of having given the testimony that sent his best friend, Vincent King, to prison decades before. And he's in overdrive protecting Duchess and her brother. Now, thirty years later, Vincent is being released. And Duchess and Walk must face the trouble that comes with his return. We Begin at the End is an extraordinary novel about two kinds of families—the ones we are born into and the ones we create.